2017
DOI: 10.18632/oncotarget.15148
|View full text |Cite
|
Sign up to set email alerts
|

Clinically relevant circulating microRNA profiling studies in pancreatic cancer using meta-analysis

Abstract: BackgroundPancreatic cancer (PaCa) is the most lethal gastrointestinal (GI) tumor. Although many studies on differentially expressed miRNAs as candidate biomarkers of pancreatic cancer have been published, reliability of these findings generated from investigations performed in single laboratory settings remain unclear.ResultsThere were 29 articles with a total of 2,225 patients and 1,618 controls included in this meta-analysis. The pooled sensitivity was 82% (95% CI, 79–85%); the specificity was 85% (95% CI, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 36 publications
1
16
1
Order By: Relevance
“…The conclusions of the current meta-analysis were similar to that of three previous meta-analysis reported by Wan et al [ 15 ], Ding et al [ 16 ], and Pei et al [ 17 ]. Compared with three previous meta-analysis above, there are a number of advantages in the meta-analysis which are as follows: (1) 40 articles with 109 studies are selected in this meta-analysis, which were more studies and participants than three previous meta-analysis; (2) more subgroup analyses than any other reported meta-analysis are performed, especially the article by Wan et al [ 15 ], including race, source of control, miRNA profiling, and the combination of miR-21; and (3) to further demonstrate the potential heterogeneity within the selected studies, our review conducted a metaregression.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The conclusions of the current meta-analysis were similar to that of three previous meta-analysis reported by Wan et al [ 15 ], Ding et al [ 16 ], and Pei et al [ 17 ]. Compared with three previous meta-analysis above, there are a number of advantages in the meta-analysis which are as follows: (1) 40 articles with 109 studies are selected in this meta-analysis, which were more studies and participants than three previous meta-analysis; (2) more subgroup analyses than any other reported meta-analysis are performed, especially the article by Wan et al [ 15 ], including race, source of control, miRNA profiling, and the combination of miR-21; and (3) to further demonstrate the potential heterogeneity within the selected studies, our review conducted a metaregression.…”
Section: Discussionsupporting
confidence: 91%
“…However, Ganepola et al reported a set of miRNAs (miR-642b-3p, miR-885-5p, and miR-22-3p) as biomarkers for the early PaC diagnosis with 0.91 SEN and 0.91 SPE [ 14 ]. So far, many studies have confirmed the diagnostic value of miRNAs in PaC [ 15 17 ]. However, there is still heterogeneity or inconsistency in the diagnostic accuracy of miRNAs, and its diagnostic value in PaC needs to be confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…In pancreatic tumor tissue, aberrant expression of miRNAs, such as miR-21, miR-221, miR-34a, and miR-217, were reported, which suggested that these molecular regulators had the potential to serve as biomarkers [17,[19][20][21]. Meta-analyses were conducted to evaluate the diagnostic value of miRNAs, and they showed moderate predictive values for PaCa diagnosis [22,23]. In each trial included in the two meta-analyses, the sensitivity and specificity of miRNAs were assessed, and one or several miRNAs with the highest diagnostic value were screened out.…”
Section: Introductionmentioning
confidence: 99%
“…The explanations for the differences include biological disparities, environmental factors, and tumor characteristics [14]. A meta-analysis by Pei et al [15] suggests significant divergences between Caucasian and Asian subgroups for circulating miRNA profiles. Given this background, the establishment of standard test and multicenter/ethnicity validation is essential to reduce the variability [16].…”
Section: Introductionmentioning
confidence: 99%